Spectra energy in cryocondensate emission nitrogen oxide and ethanol - Коршиков, Е.; Дробышев, А.; Алдияров, А.; Курносов, В.; Стржемечный, Ю.; Нaумов А.; Кимбaлл Дж.; Доaн X. (Recent Contributions to Physics, 2016)
This paper presents the experimental results obtained in the continuation of the study phenomenon cryocondensate emission. Based on the Texas Christian University held and received power characteristics cryocondensate emission arising during the condensation of nitrous oxide and ethanol. Main measurement parameters are as follows: condensation temperature T = 10 K at an initial vacuum chamber P = 10-6 Torr. As test substances, we used nitrous oxide (purity: 99.99%) and ethanol (purity: 99.99%).